233k views
0 votes
Choose the best answer​

Choose the best answer​-example-1
User Utsav T
by
5.4k points

1 Answer

6 votes


\quad \huge \quad \quad \boxed{ \tt \:Answer }


\qquad \tt \rightarrow \:-(1)/(√(3-2x))

____________________________________


\large \tt Solution \: :

We newd to find the derivative of given function :


\qquad \tt \rightarrow \: y = √(3 - 2x)


\qquad \tt \rightarrow \: y = (3 - 2x) {}^{ (1)/(2) }


\qquad \displaystyle \tt \rightarrow \: (dy)/(dx) = (d)/(dx) (3 - 2x) {}^{ (1)/(2) }


\qquad \displaystyle \tt \rightarrow \: (dy)/(dx) = (1)/(2) \sdot(3 - 2x) {}^{ - (1)/(2) } \sdot( - 2)


\qquad \displaystyle \tt \rightarrow \: (dy)/(dx) = (1)/( \cancel2) \sdot\frac{1}{(3 - 2x) {}^{ (1)/(2) } }\sdot( - \cancel2)


\qquad \displaystyle \tt \rightarrow \: (dy)/(dx) = \frac{ - 1}{ \sqrt{ (3 - 2x) {}^( )} }

Correct option : B

Answered by : ❝ AǫᴜᴀWɪᴢ ❞

User Asamoylenko
by
6.1k points